Improving the Stability of TiO2 Aqueous Suspensions by Coupling TiO2 Nanoparticles on ZrP Nanoplatelets. (August 2015) - Liu, Zhuowei; Yin, Tao; Chen, Ying; Cheng, Zhengdong; Mo, Songping; Jia, Lisi
Abstract: The stability of TiO2 aqueous suspensions is significant on catalytic efficiency for hydrogen production from water. For improving the stability of TiO2 suspensions, a new method that coupling TiO2 nanoparticles on ZrP nanoplatelets is proposed, which is differ from the traditional methods of adding various surfactants. Comparing 50 days long term stability of three samples, which are TiO2 suspensions, mixture of TiO2 and exfoliated ZrP suspensions, exfoliated TiO2 /ZrP couples suspensions, the results show that the stability of exfoliated TiO2 /ZrP couples suspensions is the best and it could keep 62% of initial concentration on the 50 th day. TiO2 nanoparticles could not aggregate into bigger particles as they are loaded on the surface of nanoplatelets is the main reason for improving stability, and the viscosity of exfoliated TiO2 /ZrP couples suspensions are much higher than TiO2 suspensions.